PENGARUH AUDIT TENURE, UKURAN KAP, SPESIALISASI AUDITOR DAN KEPENTINGAN KLIEN TERHADAP KUALITAS AUDIT DENGAN PERTUMBUHAN PERUSAHAAN, LEVERAGE, ARUS KAS OPERASI, UKURAN PERUSAHAAN, DAN KERUGIAN SEBAGAI VARIABEL KONTROL (Studi Pada Perusahaan Sektor Keuangan yang Terdaftar di BEI Tahun 2014-2017) - Riana, Novita; Amir, Hasan; Azhari, S (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the effect of audit tenure, size of kap, auditorspecialization and client importance on audit quality with company growth, leverage,operating cash flow, firm size, and losses as control variables. The population in thisstudy are financial sector companies that are listed on the Stock Exchange for the period2014-2017. The number of samples in this study were 272 companies selected throughpurposive sampling method. The analytical method used is multiple regression analysis.The proxy used to measure audit quality is the discretionary accrual of Kazsnik's model(1999). Testing in this study uses SPSS version 22 software for Windows. The resultsshowed that the audit tenure with a significant value of 0.132> 0.05 and auditorspecialization with a significant value of 0.372> 0.05 did not influence audit quality.While the size of the KAP with a significant value of 0.046 <0.05 and the clientimportance with a significant value of 0.022 <0.05 affect the audit quality. For controlvariables, company growth with a significant value of 0.559> 0.05 and firm size with asignificant value of 0.080> 0.05 did not affect audit quality. While the leverage variablewith a significant value of 0.011 <0.05, operating cash flow with a significant value of0,000 <0.05 and losses with a significant value of 0,000 <0,05 has an effect on auditquality.Keywords : audit quality, audit tenure, size of kap, auditor specialization, clientimportances, discretionary accruals.